2015
DOI: 10.1097/qai.0000000000000497
|View full text |Cite
|
Sign up to set email alerts
|

Use of Isoniazid Preventive Therapy for Tuberculosis Prophylaxis Among People Living With HIV/AIDS

Abstract: This analysis supports World Health Organization recommendations for the provision of IPT to PLHIV to reduce TB-associated morbidity and serves to highlight the need to strengthen IPT implementation. While there appears to be a greater benefit of IPT among PLHIV who are TST positive, IPT should be provided to all PLHIV without presumptive TB when TST is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 45 publications
7
29
0
Order By: Relevance
“…22,[28][29][30][31] Evidence for the added value of IPT in patients receiving ART was mostly from patients with CD4+ counts of less than 500 cells per cubic millimeter. [32][33][34][35][36][37][38] Our data are consistent with these previous studies that showed that IPT and ART have additive efficacy with respect to the prevention of tuberculosis and that suggested that the two therapies should be given concomitantly. They also highlight for countries that are reluctant to recommend IPT that isoniazid can be prescribed safely when given early in the course of HIV disease.…”
Section: Discussionsupporting
confidence: 90%
“…22,[28][29][30][31] Evidence for the added value of IPT in patients receiving ART was mostly from patients with CD4+ counts of less than 500 cells per cubic millimeter. [32][33][34][35][36][37][38] Our data are consistent with these previous studies that showed that IPT and ART have additive efficacy with respect to the prevention of tuberculosis and that suggested that the two therapies should be given concomitantly. They also highlight for countries that are reluctant to recommend IPT that isoniazid can be prescribed safely when given early in the course of HIV disease.…”
Section: Discussionsupporting
confidence: 90%
“…Isoniazid preventive therapy (IPT) decreases risk of progression from latent TB infection (LTBI) to active TB, 68 and IPT provision to high-risk groups is a cornerstone of the World Health Organization (WHO) End TB Strategy. 9,10 Despite WHO recommendations, 7 there has been limited global uptake of this intervention.…”
Section: Introductionmentioning
confidence: 99%
“…TB patients testing positive for HIV should be provided with combined antiretroviral therapy (cART), which greatly improves their survival and quality of life [7]. Testing and preventatively treating HIV and AIDS patients for TB reduces TB incidence in HIV-positives [8] and may also reduce TB incidence in the general population [9]. …”
Section: Introductionmentioning
confidence: 99%